IMPLEMENTASI SISTEM MANAJEMEN MUTU (SMM) ISO 9001:2008 PADA PENDIDIKAN VOKASIONAL - Suhadah, Suhadah; Wahyudi, Wahyudi; Sukmawati, Sukmawati (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research was conducted for the purpose of described the implementation of a Quality Management System ISO 9001:2008 at vocational school (case study at SMK N 3 Pontianak). The method used in this research is a case study. Researchers conducted a series of activities in the field, ranging from the assessment to the study site, study orientation and continued with studies focused way. In this study the data captured by the approach of in-depth interviews and observation.Data analysis techniques used Miles and Hubberman model data analysis techniques which reduction of the data, verification or presentation of the data and the withdrawal of the conclusion.  Based on data analysis, it can be concluded that the implementation of the QMS ISO 9001:2008 through eight quality management system principles at SMK N 3 Pontianak has been effective, that eight principles have been implemented simultaneously and integrated with the ISO 9001:2008 QMS principles. Therefore some obstacles faced through implemented in the eight principles QMS  of ISO 9001:2008.Some obstaclesin the eight principles include 1) customer focus, 2) leadership, 3) involving people, 4) process approach, 5) system approach, 6) continuous improvement, 7) factual decision, 8) mutually beneficial supplier relationship.Those obstacles could be concluded rever to changing attitudes, mental behavioral all the elements that exist in the school, such as low of self-initiative, sense of quality and sense of responsibility. There are some corrective action to carried out those obstacles. Moreover there are some impact which implemented QSM ISO 9001:2008 at SMK N 3 Pontianak such as quality of education graduated absorption characterized by a high rate, graduation rae each year, good working environment, external custumer satisfaction at school graduated so that can be fulfilled for customer satisfaction.        Keywords: Quality Management System (QMS), Customer Satisfaction, Vocational Education